Evolusi Paradigma Pelayanan Publik: Dari Old Public Administration hingga Network Governance - Sri Yulianty Mozin; Mohamad Nazril Abjul; Fazrurrahman Gunibala; Rosita Y. Abuba; Israh Miranti Wahab (Kajian Administrasi Publik dan ilmu Komunikasi, 2026)
Public service plays a fundamental role in fulfilling citizens’ rights and needs within modern governance systems. The increasing complexity of social, economic, and technological changes has encouraged the transformation of public administration paradigms. This study aims to analyze the evolution of public service paradigms from Old Public Administration to Network Governance, identify the key characteristics of each paradigm, and explain the shift in values and the role of the state in public service delivery. This research employs a qualitative approach using a literature review method by examining various academic sources related to public administration theories and public service governance. The analysis was conducted through content analysis and comparative analysis to identify conceptual developments and paradigm differences in public administration. The results indicate that public service paradigms have evolved from hierarchical and rule-based governance toward more collaborative and participatory governance models. Old Public Administration emphasizes bureaucratic hierarchy and administrative control, New Public Management focuses on efficiency and performance-based management, while New Public Service highlights citizen participation and democratic values. The most recent paradigm, Network Governance, promotes collaboration among government, private sector, and civil society in addressing complex public issues. These findings suggest that contemporary public administration increasingly adopts a hybrid governance approach that integrates elements of various paradigms to enhance the effectiveness and responsiveness of public service delivery.